Substrate-velocity relationships for the Trichoderma reesei cellulase-catalyzed hydrolysis of rice straw - Monterola, Conrado Pineda
The influence of substrate and enzyme concentrations on the rate of saccharification of rice straw by the cellulase enzyme system of Trichoderma reesei was evaluated. Substrate concentrations that range from 7 g/l to 25 g/l were used. The application of Michaelis - Menten Equation (MME) using the Ryu model and Etters Empirical Equation (EEE) were studied. Using the Goodness-of-Fit test, MME provided more accurate calculated reducing sugar concentration as compared to EEE. The results showed that the Apparent Michaelis Constant (K'm) of rice straw and cellulase reaction using Langmuir Method is 7.8 ± 1.0 g/l, which have a relative correlation coefficient squared (rsq) of 0.9908 and an apparent maximum reaction rate (R'max) of 0.005 g/l.hr. On the other hand EEE have rsq's ranging from 0.9417 to 0.7744. Both methods provided calculated values that are not significantly different from experimental values at 95% level. Raising the enzyme concentration from 0.0018 fpu/ml to 0.0033 fpu/ml resulted to a proportional increase in R'max from 0.005 to 0.011 g/l. hr while the K'm remains practically the same at 8.6± 1.0 g/l. Further increasing the enzyme concentration to 0.02 fpu/ml does not result in any significant increase in R'max but K'm decrease to 3.7± 1.0 g/l showing the inherent complexity of cellulase and cellulose reaction and the limitation of MME applicatio